2022
DOI: 10.3390/molecules27175675
|View full text |Cite
|
Sign up to set email alerts
|

Nutraceutical Difference between Two Popular Thai Namwa Cultivars Used for Sun Dried Banana Products

Abstract: Musa (ABB group) “Kluai Namwa” bananas (Musa sp.) are widely grown throughout Thailand. Mali Ong is the most popular Kluai Namwa variety used as raw material for sun-dried banana production, especially in the Bangkratum District, Phitsanulok, Thailand. The sun-dried banana product made from Nanwa Mali Ong is well recognized as the best dried banana product of the country, with optimal taste compared to one made from other Kluai Namwa varieties. However, the production of Mali Ong has fluctuated substantially i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(13 citation statements)
references
References 58 publications
1
12
0
Order By: Relevance
“…According to literature data, banana flesh contains various natural antioxidants, such as phenolics and vitamins. The main phenolic compounds detected in banana peel and flesh were flavonoids such as catechin, epicatechin, quercetin, myricetin, kaempferol, and cyanidin, phenolic acids such as ferulic, chlorogenic, p-hydroxybenzoic, vanillic, syringic, and p-coumaric acid and other phenolics such as lignin and tannins [ 6 , 18 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to literature data, banana flesh contains various natural antioxidants, such as phenolics and vitamins. The main phenolic compounds detected in banana peel and flesh were flavonoids such as catechin, epicatechin, quercetin, myricetin, kaempferol, and cyanidin, phenolic acids such as ferulic, chlorogenic, p-hydroxybenzoic, vanillic, syringic, and p-coumaric acid and other phenolics such as lignin and tannins [ 6 , 18 , 36 , 37 ].…”
Section: Resultsmentioning
confidence: 99%
“…In relation to this observation, the increase of antiradical and antioxidant activities at day 11 until the end of the storage period could be correlated with quercetin detection at the same period. It is reported that quercetin, which is the soluble and bound flavonoid, acts as the free radicals’ scavenger and is associated with strong antioxidant activity [ 37 , 43 ]. Furthermore, it is reported that quercetin and kaempferol have a strong effect on cardiovascular protection [ 37 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In their quantitative study of flavonoid content during the ripening process of two varieties of bananas consumed in Thailand, Wongwaiwech et al. (2022) observed similar results in relation to significant increases in the quantity of several flavonoids, for example, quercetin from 61.82 to 138.76 (124%) and 71.97 to 138.14 mg kg −1 (92%), kaempferol from 23.81 to 35.75 (50%) and 26.92 to 50.37 mg kg −1 (87%), naringenin from 77.09 to 147.23 (91%) and 67.88 to 123.45 mg kg −1 (82%), and catechin from 77.22 to 96.77 (25%) and 99.84 to 109.22 mg kg −1 (9%) throughout the ripening process in “Namwa Mali Ong” and “Nuanchan” bananas. Rutin and gallocatechin, on the other hand, had their amounts reduced from 157.40 to 136 (14%) and 202.49 to 165.6 mg kg −1 (18%) and 43.38 to 30.18 mg kg −1 (30%), and 33.77 to 15.65 mg kg −1 (54%), respectively.…”
Section: Resultsmentioning
confidence: 99%
“…This is consistent withWickramarachchi et al (2005) who found that the edible part of the banana blossom sheaths, both fresh and dried, is a source of crude ber (20.31 and 17.41 g/ 100 g of food sample, respectively) when comparing the crude ber content of the outer banana blossom sheaths (27.39 g/ 100 g of food sample) and the inner banana blossom sheaths (13.50 grams per 100 grams of food sample) with fruits and vegetables. Other types: It was found that the outer and inner banana blossom sheaths had a higher amount of crude ber than Namwa bananas, equal to 11.41 and 5.63 times, respectively (2.4 g/ 100 g of food sample)(Wongwaiwech et al, 2022), more than dragon fruit, equal to 12.80 and 6.31 times, respectively (2.14 grams per 100 grams of food sample), 14.65 and 7.22 times more than durian pulp, respectively (1.87 g/ 100 g of food sample)(Nitithan et al, 2004), and 2.77 and 1.37 times more than ginger, respectively (9.87 grams per 100 grams of food sample)(Madhu et al, 2017). It was found that the outer sheaths of banana blossoms were the source of crude ber and total carbohydrates.…”
mentioning
confidence: 99%